Instilling Religious Values Through Songs in Forming Social Bonds at West Kalimantan State Middle Schools - Sagala, Mastri Dihita (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2025)
Instilling religious values is important to implement early, even during children's development and growth. Music, which has numerous benefits, can be an effective strategy in instilling those religious values. This research discusses the instillation of religious values implemented through singing activities using the